Paternal perinatal depression: A concept analysis - Jianfei Chen; Jing Zhao; Xiaoli Chen; Zhijie Zou; Zhao Ni (Wiley, 2023)
Abstract Aim Our aim is to clarify the concept of paternal perinatal depression including its definition, attributes, antecedents and consequences. Design A concept analysis. Methods To obtain relevant evidence, several databases were searched systematically including PubMed, EMBASE, Web of Science, CINAHL, PsycINFO and the Cochrane Library. Qualitative or quantitative articles published in English that focused on paternal perinatal depression were included. After the literature quality assessment, Walker and Avant's concept analysis strategy was used. Results Five defining attributes (i.e. symptoms occur during the partner's pregnancy or 1‐year postpartum and last at least 2 weeks, emotional symptoms, somatic symptoms, negative parenting behaviours and 'masked' symptoms), four antecedents (i.e. personal issues, pregnancy‐related issues, infant‐related issues, social issues) and three consequences (i.e. offspring outcomes, marital relationship, maternal negative emotions) were identified.